Aplicación de la gestión por procesos en la microempresa "Creaciones Nataly" ubicado en la ciudadela El Recreo en el Sur de Quito - Sunta González, Verónica Nathaly (2011)
Ecuador is a country that is immersed in the globalization of markets, and the great competition there; that is why the application of tools and methods to ensure and control the productivity of these methods is necessary to take advantage of our competitors, is the "Application Process Management" Process management in our country has not It has been well received, and it is up to the globalization of markets when organizations see the need to be competitive to stay alive in this environment.